CRISPR-Cas12a exhibits metal-dependent specificity switching - Nguyen, Giang T; Schelling, Michael A; Raju, Akshara; Buscher, Kathryn A; Sritharan, Aneisha; Sashital, Dipali G (Nucleic acids research, 2024)
Cas12a is the immune effector of type V-A CRISPR-Cas systems and has been co-opted for genome editing and other biotechnology tools. The specificity of Cas12a has been the subject of extensive investigation both in vitro and in genome editing experiments. However, in vitro studies have often been performed at high magnesium ion concentrations that are inconsistent with the free Mg2+ concentrations that would be present in cells. By profiling the specificity of Cas12a orthologs at a range of Mg2+ concentrations, we find that Cas12a switches its specificity depending on metal ion concentration. Lowering Mg2+ concentration decreases cleavage defects caused by seed mismatches, while increasing the defects caused by PAM-distal mismatches. We show that Cas12a can bind seed mutant targets more rapidly at low Mg2+ concentrations, resulting in faster cleavage. In contrast, PAM-distal mismatches cause substantial defects in cleavage following formation of the Cas12a-target complex at low Mg2+ concentrations. We observe differences in Cas12a specificity switching between three orthologs that results in variations in the routes of phage escape from Cas12a-mediated immunity. Overall, our results reveal the importance of physiological metal ion conditions on the specificity of Cas effectors that are used in different cellular environments. Lay Summary CRISPR-Cas systems are commonly used for biotechnology. Their specificity has been studied extensively and has previously been thought to be well understood. In this work, we asked a simple question about the effect of metal ion concentration on CRISPR specificity; the results are surprising and striking. At the actual metal ion concentrations found in cells, Cas12a specificity is inverted in comparison to the higher metal ion conditions that are typically used in test-tube assays. The specificity observed at lower metal ion concentration is more relevant under cellular conditions. Graphical Abstract Graphical Abstract